Combined adenovirus-mediated artificial microRNAs targeting mfgl2, mFas, and mTNFR1 protect against fulminant hepatic failure in mice. - Dong Xi; Ming Wang; Huali Ye; Xiaoping Luo; Qin Ning (PLoS ONE, 2013)
Hepatitis B virus (HBV)-related acute-on-chronic liver failure (ACLF) has a poor prognosis with high in-hospital mortality. Hepatic and circulating inflammatory cytokines, such as fibrinogen like protein 2 (fgl2), FasL/Fas, and TNFα/TNFR1, play a significant role in the pathophysiology of ACLF. This study aimed to investigate the therapeutic effect of recombinant adenoviral vectors carrying constructed DNA code for non-native microRNA (miRNA) targeting mouse fgl2 (mfgl2) or both mFas and mTNFR1 on murine hepatitis virus (MHV)-3-induced fulminant hepatitis in BALB/cJ mice. Artificial miRNA eukaryotic expression plasmids against mfgl2, mFas, and mTNFR1 were constructed, and their inhibitory effects on the target genes were confirmed in vitro. pcDNA6.2-mFas-mTNFR1- miRNA，which expresses miRNA against both mFas and mTNFR1 simultaneously，was constructed. To construct a miRNA adenovirus expression vector against mfgl2, pcDNA6.2-mfgl2-miRNA was cloned using Gateway technology. Ad-mFas-mTNFR1- miRNA was also constructed by the same procedure. Adenovirus vectors were delivered by tail-vein injection into MHV-3-infected BALB/cJ mice to evaluate the therapeutic effect. 8 of 18 (44.4%) mice recovered from fulminant viral hepatitis in the combined interference group treated with Ad-mfgl2-miRNA and Ad-mFas-mTNFR1-miRNA. But only 4 of 18 (22.2%) mice receiving Ad-mfgl2-miRNA and 3 of 18 (16.7%) mice receiving Ad-mFas-mTNFR1- miRNA survived. These adenovirus vectors significantly ameliorated inflammatory infiltration, fibrin deposition, hepatocyte necrosis and apoptosis, and prolonged survival time. Our data illustrated that combined interference using adenovirus-mediated artificial miRNAs targeting mfgl2, mFas, and mTNFR1 might have significant therapeutic potential for the treatment of fulminant hepatitis.